Urban Soundscapes. A Soundscape Design Framework for Urban Open Public Spaces. - Kang, Jian (Technische Hochschule Ostwestfalen-Lippe, IDS Institut für Designstrategien, 2021)
While noise is often the most complained about environmental problem, with a social cost of 0.2-2% of GDP in Europe, conventional engineering approaches of merely reducing noise level often does not deliver an improved quality of life (Kang, 2007). The soundscape strategy, by integrating wanted sounds as ‘resources’ and by considering sound environment as perceived rather than just physical properties, in context, with an interdisciplinary approach, is a growing field for addressing this gap (ISO, 2014), for health promotion/restoration, cultural preservation, social integration, cost-effective development, and ecological sound source diversity (Kang and Schulte-Fortkamp, 2016). Urban open public spaces are important components of a city. The European Environmental Noise Directive (EU, 2002) introduced a new strand of work relating to ‘quiet areas’, which is also important for policies affecting urban open public spaces. It is important to put soundscape into the intentional planning and design process comparable to landscape, integrating the theories of soundscape. In this article, a framework on key factors for soundscape planning and design in urban open public spaces is discussed, and correspondingly, the potentials of planning and designing key components for soundscape, namely sounds, space, people and environment (Kang, 2007), are explored.
Keywords: Stadtplanung; Geräusch; Klang; Ressource; Akustik; Gestaltungselement; Öffentlicher Raum; Lärmschutz; Soundscape